DESAIN UNIT TEKAN UTAMA MESIN PAVING BLOCK OTOMATIS - Harry Harry Laksono Nugroho; Didit Setyo Pamuji (Retii, 2021)
The main press unit is the main part of the paving block printing machine using hydraulic power and a vibrator which is the development of the manual paving block printing machine. Currently, paving block printing machines which are usually carried out by workers manually have begun to be abandoned because the quality produced does not meet the SNI 03-0691-1996 standard and the demand is increasing. The purpose of this Main Press Unit design design is to design a paving block printing machine that can reach K400 quality and the amount of 100 m2 in a day. The main component design of the main press unit for the K400 type paving block printing machine (compressive strength 400 kg/cm2) consists of a middle hydraulic press with a pressure capacity of 10 MPa (compressive force of 12560 N with a bore diameter of 40 mm), two hydraulic side arm drives with 3.5 MPa capacity, two rear hydraulics driving the feeding box with a capacity of 3.5 MPa, main frame, upper mold, lower mold, lower mold vibrating table, upper mold vibrator, feeding box, and side molding drive arm. The total power requirement for all hydraulics is 1.606 kW (2.087 hp), while the total power requirement for the vibrator system is 1.47 kW (1.96 hp). This main press unit machine with a hydraulic pressure of 10 Mpa and with 15 pieces of mold can make paving blocks with K400 quality with a capacity of up to 100 m2 or more per day. The paving block materials used are; fine sand : coarse aggregate : fine aggregate : water plus concrete hardener ie 1/2 : 1 : 1 : 1/4.